[tex]v_{1}^2-v^2=2as[/tex] (1)
[tex]v_{2}^2-v_{1}^2=2as[/tex] (2)
[tex]v_{3}^2-v_{2}^2=2as\Rightarrow -v_{2}^2=2as[/tex] (3)
(2)-(3)[tex]=>2v_{2}^2-v_{1}^2=0\Leftrightarrow (\sqrt{2}v_2-v_1)(\sqrt{2}v_2+v_1)=0\Leftrightarrow \sqrt{2}v_2-v_1=0\Leftrightarrow v_1=\sqrt{2}v_2[/tex]
Mặt khác: [tex]a=\frac{v_2-v_1}{1}=\frac{0-v_2}{t_3}\Leftrightarrow \frac{\sqrt{2}-1}{1}=\frac{1}{t_3}\Rightarrow t_3=\frac{1}{\sqrt{2}-1}[/tex]
Tương tự: Ta cũng có [tex](1)-(2)\Leftrightarrow 2v_1^2-v^2-v_2^2=0\Leftrightarrow 4v_2^2-v^2=0\Rightarrow 2v_2=v[/tex]
[tex]a=\frac{v_1-v}{t_1}=\frac{-v_2}{1+\sqrt{2}}\Leftrightarrow \frac{v_2(\sqrt{2}-2)}{t_1}=\frac{-v_2}{1+\sqrt{2}}\Rightarrow t_1=\sqrt{2}[/tex]
với v,v1,v2,v3 ; t1;t2;t3 lần lượt là vận tốc và thời gian của đoạn 1 2 3